Bee-keepers’ Spell in Ukrainians’ World-View Practice: the Magical Power of a Word - Мовна, Уляна (Poznańskie Studia Slawistyczne, 2012)
The article is exposing some results of the study in bee-keepers’ spell as a featuring trait of Ukrainians’ world-view practice; the present research is the first work of such a kind in the home ethnology. The spell belongs to that sort of ritual text that might be characterized by a vivid and most active speech with its fully evident magical strength. Spell as a genre of folklore refers to peculiar items owing to its archaic nature as well as to utilitarian functionalism, especially verbal destination, unity of sacral and profane articulation. The world-view ground of spell has been always heterogeneous as that originated and developed through the ages with fixing so prime of human world-consciousness as historically later (Christian) epistemological and axiological picture of the reality. In the paper the bee-keepers’ spell has been considered because of its religious and magical contents that has quite significant spread so in everyday bee-keeping practice (occasional aspect), as in the contents of yearly religious festivals (the calendar one). The aim of bee-keepers’ spell has been getting a concrete practical result, i.e. successful functioning of apiary.